2006
DOI: 10.1002/ptr.1943
|View full text |Cite
|
Sign up to set email alerts
|

CKBM stimulates MAPKs but inhibits LPS-induced IFN-γ in lymphocytes

Abstract: CKBM is an herbal formula composed of five Chinese medicinal herbs (Panax ginseng, Schisandra chinensis, Fructus crataegi, Ziziphus jujuba and Glycine max) supplemented with processed Saccharomyces cerevisiae. It has been demonstrated that CKBM is capable of triggering the release of IL-6 and TNFalpha from human peripheral blood mononuclear cells. In this report, T-lymphocytic Sup-T1 cells and B-lymphocytic Ramos cells were utilized as cellular models to investigate how CKBM regulates intracellular signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…KIOM-79 might mediate its anti-diabetic action by inhibiting the PKC-␣/␤ ␣ and p38MAPK signaling pathway, in turn inhibiting VEGF expression in human RPE cells. In contrast, Chan et al (2006) reported that a herbal formula composed of five herbs (Panax ginseng, Schianadra chinensis, Fructus crataegi, Ziziphus jujube, and Glycine max) stimulated MAPK in lymphocytes. Different components of herbs may have different chemical constitutes, mechanisms, and effects in various diseases.…”
Section: Discussionmentioning
confidence: 85%
“…KIOM-79 might mediate its anti-diabetic action by inhibiting the PKC-␣/␤ ␣ and p38MAPK signaling pathway, in turn inhibiting VEGF expression in human RPE cells. In contrast, Chan et al (2006) reported that a herbal formula composed of five herbs (Panax ginseng, Schianadra chinensis, Fructus crataegi, Ziziphus jujube, and Glycine max) stimulated MAPK in lymphocytes. Different components of herbs may have different chemical constitutes, mechanisms, and effects in various diseases.…”
Section: Discussionmentioning
confidence: 85%
“…As far as the mechanism of action of fatty acids is concerned, it has been well established that they interfere with cell signalling, particularly with the cascade of MAP kinases like ERK1/2 and p38 [42,43]. In fact, Chan et al [18] have also demonstrated that a mixture of herbs containing Zizyphus extracts also interfere with the phosphorylation of ERK1/2 and p38 in T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adhvaryu et al [17] have shown that Zizyphus extracts alongwith other plants stimulated neutrophil functions and exerted hepatotoxic and immunomodulatory effects in guinea pigs. Chan et al [18] assessed cell signaling mechanisms in T-cells and provided the evidence that a mixture of herbs containing Zizyphus extract induced the expression of mitogen-activated protein kinases ( i.e . ERK, JNK and p38) in T-cells, indicating that the immunomodulatory effects of Zizyphus involve the activation of second messenger cascade.…”
Section: Introductionmentioning
confidence: 99%
“…LPS administration in vivo increases systemic levels of numerous inflammatory cytokines, including TNF-␣, IL-1, IL-6, and IFN-␥ (4,15,40). A rise in plasma IL-6 levels was confirmed in our experiments ( Table 2).…”
Section: Il-6 and Ifn-␥-induced Apelin Expression And Blockade Of Jakmentioning
confidence: 99%
“…Additionally, the influence of lipopolysaccharide (LPS) on enteric apelin expression was examined. LPS administration to rodents promotes systemic inflammation and will activate host immune and inflammatory cells, resulting in elevations of tissue and systemic levels of numerous cytokines, including TNF-␣, IL-1, IL-6, and IFN-␥ (4,15,24,33,40). The roles of the Jak/Stat signaling pathway and of a putative Stat3 binding site in the rat apelin core promoter in cytokine-and LPSinduced apelin transcriptional activity were also examined.…”
mentioning
confidence: 99%